Hasan Hanafi’s Perspective Soul Theory - Syah, Ahmad Maujuhan; Christoph, Nash; Rosario, France Tamara (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
The soul does have its magnetic power, so discussions about the soul will continue as long as humans live. If abstract, it cannot be seen or felt but is believed to exist. Debates between scientists are commonplace about whether the soul exists or whether the soul is just a discussion of humans who cannot discuss what is experienced. This research uses a descriptive qualitative method. Qualitative research does not carry out calculations in carrying out epistemological justification. Hasan Hanafi in this includes the soul in the formulation of theology. In Hasan Hanafi's theology, Hanafi tries to reconstruct theology by reinterpreting classical theological themes in a metaphorical-analogical way. Below are explained three important Hanafi thoughts related to the themes of kalam; the substance of God, the attributes of God and the Problem of Monotheism